The Middle Class In Southeast Asia: Diversities, Identities, Comparisons And The Vietnamese Case - T. King, Victor (Penerbit Universiti Sains Malaysia (USM Press), 2008)
Much interest has been devoted since the 1980s to the new urban, educated middle class in Southeast Asia which has emerged primarily as a result of stateled modernization and capitalist transformation. These processes have also been occurring recently in the former centralized socialist economies of Southeast Asia mainland. However, there has not been a great deal of comparative region-wide research on the new middle class and we still know very little about such countries as Vietnam. As Lui proposes we must explore the "richness of class analysis….by probing people's values, outlook, lifestyles, moral perspectives, perceptions of social change and political choices" (2006: 47). As part of a research project which examines the diversities and changing identities of the new middle class in the region, this paper presents some initial thoughts on the problems of defining and delimiting the middle orders of society and some preliminary findings on the young educated middle class in the hitherto neglected case of Vietnam.